PERANCANGAN PRESS HYDRAULIC SEBAGAI ALAT BANTU PROSES PRODUKSI DI PT PIPA MAS PUTIH BATAM - ALUMAN MANURUNG, KEVIN; Sirait, Ganda (Computer Science and Industrial Engineering, 2022)
The Production Department at PT PIPA MAS PUTIH has production process constraints, especially in the Wire Mesh assembly process. Based on this, the researcher intends to conduct research on the design of this Wire Mesh product using the Design for Manufacture and Assemby (DFMA) method. This study aims to make a design and compare between the initial design and alternative designs based on the results of the evaluation of the initial design using DFMA and based on comparison parameters so that they can determine the best design choice. Based on the DFMA analysis of the initial design, it was found that the components of the Wrapping machine consisted of 25 components with a weight of 556.3 kg and a total cost of Rp. 61,465,000. The alternative designs designed were analyzed using DFMA and the results obtained were 102 components of the Wrapping machine with a weight of 84,475 kg, a total machining time of 8.91 hours and a total cost of Rp. 29,047,000. From the initial design and the alternative design of the Wrapping machine that was designed, after being compared based on the parameters of the number of components, total weight, total cost, machine efficiency function. the results of processing selected the best alternative design.